Students' Quantitative Literacy in Solving PISA Problem Based on Gender Differences - Lestariningsih Lestariningsih; Nita Safitri Maulidah; Moch. Lutfianto (Universitas Hamzanwadi, 2021)
Quantitative literacy is an important skill needed by individuals in solving problems with quantitative situations in daily life. Thus, this paper aimed to identify quantitative literacy in solving the PISA problem based on gender differences. This study used descriptive research with a qualitative approach. Research subjects in this study were two tenth-grade students in middle school. They were one male student and one female student who have the similar mathematical ability. Data were collected by giving the Program for International Student Assessment (PISA) problem, especially mathematical literacy, and using the interview method. The research results showed that the quantitative literacy of male student in solving PISA problems is by using fewless symbols to represent time and incomplete algorithms and procedures. In comparison, the quantitative literacy of female student in solving PISA problems is by using a more detailed description, more mathematical operations, and solving the problem according to algorithms and procedures. Furthermore, both students have quantitative literacy aspects, including interpretation, calculation, representation, assumption, analysis, and communication skills. Therefore, the quantitative literacy ability of students can be used as a reference for teachers to determine the modeling activities conducted by students in solving the PISA problem.